Evaluation of Pharmacological Potential of Fruits of Solanum Xanthocarpum - Natarajan Sampathkumar, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Evaluation of Pharmacological Potential of Fruits of Solanum Xanthocarpum